PENDAMPINGAN KELOMPOK PKK DALAM USAHA OPTIMALISASI PENGELOLAAN SAMPAH ORGANIK DAN ANORGANIK DOMESTIK MENUJU DESA MANDIRI SAMPAH - Widiyanto, Agnes Fitria; Kuswanto, Kuswanto; Yunirno, Saudin (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2015)
ABSTRACTBased on surveys and in-depth interviews with Grendeng people, the management of waste has been collected by type of waste, but the waste is re-mix when it transported. The waste is piled, bad smell, cause accidents like glass and make the vectors of disease comes. The purpose of the research is to find out the problems faced by the PKK to handle the waste organic and domestic an-organic problem in Grendeng in anattempt to realize the independent village of waste. The method used is descriptive qualitative. Subjects were obtained by using purposive sampling as many as 8 informants. The way to collect the data were using in-depth interviews and observation. Validity test used in this research is triangulation technique. The result of this research indicate that the problems faced by the PKK are information about waste collection, transporting, dumping, handling and processing of the final stages of waste. In addition, the group of PKK need the assisting to realize the independent village of waste by cooperating with institutions, students, other members of the PKK and Grendeng peoples.Keywords : Assisting the PKK, Management of Waste, Independen Village of Waste Kesmasindo, Volume 7, Nomor 2, Januari 2015, Hal. 106-117